Changes in DNA 5-Hydroxymethylcytosine Levels and the Underlying Mechanism in Non-functioning Pituitary Adenomas - Xu, Yiwen; Niu, Yamei; Deng, Kan; Pan, Hui; Feng, Feng; Gong, Fengying; Tong, Wei-Min; Chen, Shi; Lu, Lin; Wang, Renzhi; You, Hui; Yao, Yong; et al. (Frontiers in Endocrinology, 2020)
Epigenetic factors have been proven to contribute to pituitary adenoma formation. 5-hydroxymethylcytosine (5hmC), which is catalyzed by ten-eleven translocation 2 (TET2), is related to DNA demethylation. In order to explore the pathogenesis of non-functioning pituitary adenomas (NFPAs), we detected genomic 5hmC levels in 57 NFPAs and 5 normal pituitary glands, and TET2 expression, distribution and TET2 alteration. Genomic 5hmC levels in NFPAs were significantly lower than those in normal pituitary glands (0.38‰ (0.24‰, 0.61‰) vs. 2.47‰ (1.56‰, 2.83‰), P < 0.0001). There was positive correlation of 5hmC levels with TET2 total and nuclear expression in NFPAs (r = 0.461, P = 0.018; r = 0.458, P = 0.019). Genomic 5hmC levels in NFPAs with TET2 p.P29R were significantly lower than those in wild type NFPAs (0.33 ± 0.18‰ vs. 0.51 ± 0.25‰, P = 0.021). We found genomic 5hmC loss in human NFPAs for the first time. Genomic 5hmC levels may be affected by TET2 expression, subcellular localization and TET2 mutation.